Latin America's Position in the Context of Globalization - Bernal Pulido, Carlos (2005)
Globalisation is driving the abandonment of the traditional Keynesian-Westphalian model, which recognised the state as an optimal entity for organising the public sphere and administering justice. It is therefore necessary to determine which model would be appropriate in the context of globalisation for Latin America to be able to participate on equal terms in discussions on distributive justice and recognition. Furthermore, it is crucial to consider how this new framework should be constructed and what rules should regulate it in order to guarantee equitable political representation. To that extent, this paper addresses three key problems related to the lack of equal political representation in Latin America in the context of globalisation. These problems are: (i) the deficit of political representation in the construction of the globalisation framework, (ii) the deficit of political representation and equitable enjoyment of freedoms and social rights, and (iii) the deficit of political representation caused by emigration. The three factors examined here impede the capacity of Latin American citizens to provide informed consent to the emerging decisions of globalisation, despite being directly affected by them. Upon completion of this investigation, a series of methodological proposals will be presented with the aim of addressing and potentially rectifying the aforementioned deficiencies in representation.